Description of a new species of Laspeyresiini, Lathronympha sardinica sp.n. (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Tortricidae, Lathronympha sardinica sp.n., is described. The new species was collected in the mountains of Gennargentu, Sardinia (Italy).
Keywords: Lathronympha sardinica; Lepidoptera Tortricidae; new species; Sardinia